HUBUNGAN KUALITAS AIR TERHADAP EKTOPARASIT PADA IKAN KAKAP PUTIH (Lates calcarifer) DI TAMBAK SOBO - Munir, Muh. Syahrul (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
Barramundi (Lates calcarifer) is one of the leading marine aquaculture commodities in Indonesia. One of the main challenges in farming white snapper is fish mortality caused by ectoparasite infestations. Ectoparasite infestations are closely linked to environmental factors within aquaculture systems. This study aims to identify the types of ectoparasites found in white snapper (Lates calcarifer) ponds, to assess the water quality conditions at PT. Suri Tani Pemuka, Sobo Unit, and to analyze the correlation between water quality parameters and the prevalence of identified ectoparasites. The sampling method used was simple random sampling across six pond units. Data collection was conducted through direct observation and field surveys. The results revealed the presence of two ectoparasites: Dactylogyrus sp. and Cryptocaryon irritans. Water quality conditions in the white snapper ponds at PT. Suri Tani Pemuka, Sobo Unit, showed that parameters such as temperature, dissolved oxygen, pH, and salinity were within the optimal range for white snapper aquaculture. However, nitrite and ammonia levels exceeded the optimal standards. The correlation analysis between water quality parameters and the prevalence of Dactylogyrus sp. indicated no significant relationship for temperature, dissolved oxygen, salinity, pH, nitrite, or ammonia. In contrast, the correlation between water quality parameters and the prevalence of Cryptocaryon irritans showed that temperature, dissolved oxygen, nitrite, and ammonia had no significant correlation, whereas pH and salinity exhibited a significant correlation with the prevalence of Cryptocaryon irritans.